THE COMPOSITION OF SPECIES AND STRUCTURE OF SEAGRASS FISH COMMUNITY IN TANJUNG TIRAM – INNER AMBON BAY - Husain Latuconsina; M. Natsir Nessa; Rohani Ambo Rappe (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
The study was conducted in March - May 2011 in the coastal waters of Tanjung Tiram – inner Ambon bay. The aims of the study were to determine the composition of species and structure of fish communities in seagrass beds ecosystems. Fish were collected every spring and neap tide for three month periode with a swept area method using beach seine. Fishes were collected as many as 6444 individuals representing 68 species from 29 families. Siganus canaliculatus was contributed up to 62.91% of the total individual fish found.The fish community structure was varied between spring and neap tide. Index of dominance was in low category, diversity in medium, and evenness in unstable conditions. Moreover, the results indicated that seagrass ecosystems in Tanjung Tiram (TAD) have an important role as spawning, nursery ground, and feeding ground. Therefore, management and conservation efforts are urgently needed to maintain the ecological role of seagrass ecosystems for the sustainability of the fish resources.Keywords: Seagrass beds, fish community, tanjung tiram, inner Ambon Bay